2015
DOI: 10.1016/j.celrep.2015.09.059
|View full text |Cite
|
Sign up to set email alerts
|

Bactericidal Antibiotics Induce Toxic Metabolic Perturbations that Lead to Cellular Damage

Abstract: Summary Understanding how antibiotics impact bacterial metabolism may provide insight into their mechanisms of action and could lead to enhanced therapeutic methodologies. Here, we profiled the metabolome of Escherichia coli after treatment with three different classes of bactericidal antibiotics (beta-lactams, aminoglycosides, quinolones). These treatments induced a similar set of metabolic changes after 30 minutes that then diverged into more distinct profiles at later timepoints. The most striking changes c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

32
347
2
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 409 publications
(405 citation statements)
references
References 95 publications
32
347
2
1
Order By: Relevance
“…It is the amount and target of Fenton oxidants that are relevant for antibiotic lethality, not the intracellular levels of endogenously produced O 2 − or H 2 O 2 . These and other results suggest that the incorporation of oxidized nucleotides into nascent DNA followed by incomplete base excision repair (BER) is an important molecular mechanism that contributes to the ROS-dependent component of antibiotic lethality (11,12,14,18). To date, no alternative interpretation has been suggested for this body of experimental observations.…”
Section: Significancementioning
confidence: 86%
See 3 more Smart Citations
“…It is the amount and target of Fenton oxidants that are relevant for antibiotic lethality, not the intracellular levels of endogenously produced O 2 − or H 2 O 2 . These and other results suggest that the incorporation of oxidized nucleotides into nascent DNA followed by incomplete base excision repair (BER) is an important molecular mechanism that contributes to the ROS-dependent component of antibiotic lethality (11,12,14,18). To date, no alternative interpretation has been suggested for this body of experimental observations.…”
Section: Significancementioning
confidence: 86%
“…It is particularly relevant that nucleoside triphosphates and nucleic acids are anionic ligands that complex with Fe +2 and promote the Fenton reaction to an extent comparable to EDTA and nitrilotriacetate (38,41). Furthermore, the proximity of the nucleic acid base of a dNTP or NTP to an Fe +2 complexed by its phosphates (42) favors its reaction with highly reactive Fenton oxidants (11,16). Since the diffusion distance for a hydroxyl radical is only one carbon bond length (43), nucleotides and nucleic acids must be at higher risk of damage from Fenton oxidants than many other biomolecules because of their ability to complex Fe +2 and promote local production of Fenton oxidants.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent study showed that, to survive sub-lethal concentrations of antibiotics, E. coli cells up-regulate their DNA/RNA repair (Belenky et al, 2015). This is thought to drain the nucleotide pools as they are immediately used for DNA/ RNA repair.…”
Section: Discussionmentioning
confidence: 99%